Analisis Implementasi Permendagri No. 19 Tahun 2016 di Provinsi Sumatera Utara - Ranto Mahmuda Perdana Aritonang; Badaruddin; R. Hamdani Harahap (Universitas Medan Area, 2023)
The purpose of this research is to analyze the implementation and obstacles of Permendagri No. 19 of 2016 concerning the management of regional assets at the Regional Tax and Levy Management Agency of North Sumatra Province. The research method used in this research is field research with a qualitative research approach, with a descriptive type of research. The results of the study show that from communication, it needs to be improved. Resources, Placement of human resources for goods management through the appointment and proposal by the Head of the Agency and then determined through a Governor's Decree. disposition. It's good enough even though it must always be fostered and reminded of its main duties, especially the Goods Management team, Bureaucratic Structure (Fragmentation and SOP), Although the number of Goods Managers is quite large but not yet fully effective, where there are still some goods managers both in the Agency and in the UPT are still working on things -Things that are outside of their main function.